Spouses' Access to Financial Services: Estimating Technological and Managerial Gaps in Production - Maria Luz L. Malabayabas; Ashok K. Mishra; Joaquin Mayorga (Institute of Labor Economics (IZA), 2023)
The study investigates the effect of the spouse's access to financial services (credit or savings) through membership in a self-help group on adopting technology, technical efficiency, and managerial gaps. To estimate the empirical model, we use farm-level data from rice farming households in eastern India, propensity score matching method, and selectivity-corrected stochastic production frontier. Results show that families with access to financial services via a spouse's membership in self-help groups have slightly higher technical efficiency than their counterparts. Both technology and managerial gaps are higher for farms where spouses have access to financial services via SHGs than their counterparts. With access to financial services via spouses, rice farmers used more hired labor, about 1.3 person-days/ha for crop establishment. Thus, women joining self-help groups can increase farm productivity, and extension agents should also focus on spouses and their role in farming decision-making, not just financial management.
Keywords: C21; Q12; Q16; Q55; R58; 330; self-help group; PSM; selection-correction SPF; production efficiency; hired labor